Pemanfaatan Running text Sebagai Media Informasi Waktu Solat Dilengkapi Tartil Otomatis di Mushalla Darul Falah Solok Selatan - Edwar Rosman; Katrina Flomina G; Miftahul Hasanah; Widya Febriani; Yerri Kurnia Febrina; Eva Oktavia; Muhammad Ibrahim Nasution; Taruma Leo Wijaya (Politeknik Piksi Ganesha Indonesia, 2025)
Musala Darul Falah is a place of worship for Muslims located in Jorong Koto Tuo, Nagari Lubuk Malako, Sangir Jujuan District, South Solok Regency. The mosque is regularly visited by the local community for the five daily prayers, and it also hosts routine religious classes for children and teenagers. Currently, the prayer schedule at Musala Darul Falah is still managed using a conventional method, specifically a chalkboard. If there are any changes in the prayer times, they must be manually updated. The appearance of the prayer schedule board is quite basic and lacks an aesthetic appeal. In fact, places of worship should incorporate elements of beauty to enhance the comfort of the congregation during prayer. To address this issue, the management of Musala Darul Falah, in collaboration with the Community Service Team, has installed a digital prayer schedule display in the form of a running text device with an automatic call-to-prayer feature. This device can be accessed and controlled through a smartphone. The design and appearance of the content displayed on the running text can be customized by the management according to their preferences. With the installation of this running text device, it is hoped that the management of Musala Darul Falah will have a more efficient way to manage the prayer schedule and add an aesthetic touch to improve the comfort of the congregation